WACANA POSTMODERNISME: ANALISIS DIALEKTIK TERDAHAP BUDAYA, FILSAFAT DAN MANIFESTASINYA PADA TEOLOGI KONTEMPORER - Yosep Belay; Ferry Simanjuntak; Solihin Bin Nidin; Susan Setiawan (Manna Rafflesia, 2023)
Human culture and its components move dynamically according to the trend of philosophical ideas that drive it. The existence of the church, which is also the subject and object of culture, is also conditioned on it. In the present context, postmodern philosophy and culture pose severe challenges to the church in two categories: it's cultural product components and philosophical ideas. These two issues are the subject of research that the author examines in this article to describe the challenges of postmodern culture and philosophy for the church. The research method used by the author is descriptive qualitative, with the study of primary and secondary data sources using literature studies and phenomenal hermeneutics. The results of this study indicate that postmodern philosophy and culture have seriously impacted the church today. Postmodern philosophical ideas radically reject claims of absolute truth and challenge the nature of language and the principles of traditional Christian hermeneutics. Meanwhile, its cultural products affect the practical application of church services to the lifestyle of God's people, both positively and negatively.